Epichloë bromicola from wild barley improves salt-tolerance of cultivated barley by altering physiological responses to salt stress - Wang, Zhengfeng; Liu, Jing; White, James F.; Li, Chunjie (Frontiers in Microbiology, 2022)
Epichloë bromicola is a cultivable fungal endophyte that lives in symbiosis with wild barley (Hordeum brevisubulatum) to which it confers salt tolerance. This study tested the hypothesis that E. bromicola derived from wild barley has the potential to increase salt tolerance in cultivated barley under salt stress. To test this hypothesis, growth response, physiological parameters, and metabolic profiles of barley plants inoculated with E. bromicola (E+) and those not inoculated (E-) were compared under salt stress. Compared to E- barley plants, E+ barley plants had significantly increased plant height, shoot biomass, total biomass, chlorophyll content, osmotic synthesis, and accumulation of stress-adaptation metabolites. E. bromicola increased the salt stress tolerance of cultivated barley, and the positive effects correlated with different salt stress conditions. These results suggest that E. bromicola has promising potential for enhancing the salt tolerance of barley. New insights regarding the mechanisms underlying this barley-fungal endophyte association is provided and interesting questions regarding the role of E. bromicola in fungal enhanced tolerance to salt stress in this symbiosis are raised.